Emerging Environmental Technologies - Shah, Vishal (Springer Netherlands : Imprint: Springer, 2008)
With increasing attention being paid to the changing environment and the underlining reasons from the change, scientists are working at a faster pace to invent technologies that could have a positive impact. This book exclusively focuses on the technologies that would be in the forefront in near to far future. Each and every article in the book is peer-reviewed and discusses the current environmental challenges, the novel innovation and future directions. The topics covered in the book include microbial fuel cells, hybrid solar lighting, bacterial swimming for environmental remediation, cleaner engines, nanoparticles for effluent treatment, surface catalysis and proteins as gas hydrates inhibitors. This book will be suitable for academicians, industries and governmental/non-governmental agencies in the field of environmental sciences and technology.